Efeitos de um metal essencial (Mn) e um não essencial (Cr), isolados e em mistura, na clorofícea de água doce Raphidocelis subcapitata - Alho, Lays de Oliveira Gonçalves (2022)
Metal contamination of aquatic ecosystems poses to aquatic biota. Usually, metals are not present isolated in environments, so aquatic organisms are exposed to several chemical compounds simultaneously. Despite this, there is still not much data on the long-term effects of metal mixtures on aquatic organisms. This study investigates the toxic effects of an essential metal, manganese (Mn), and a non-essential one, chromium (Cr), in single and combined form, on the freshwater chlorophyte Raphidocelis subcapitata. This research evaluated the impact of the metals in isolated and mixture forms on growth, the photosynthetic activity, biochemical composition, and reactive oxygen species (ROS) production of this chlorophyte to obtain an in-depth assessment of the toxic actions of the contaminants. Both Mn and Cr led to growth inhibition and reduced the chlorophyll a fluorescence of the microalgae, being Mn more toxic than Cr. The species sensitivity distribution curve revealed that the species used in the present study was the most sensitive to Mn, among other several freshwater organisms exposed to this metal. Mn negatively affected the efficiency of the oxygen evolution complex, the effective quantum yield, and photochemical quenching of the microalgae. At the same time, Cr led to less severe alterations in these parameters, probably due to the activation of photoprotection mechanisms. The mixture of Mn and Cr showed additive effects for the microalgae, and the Independent Action reference model was the one that best fitted the data. The ROS production increased significantly after 96 h of exposure to both metals. At high Mn concentrations (7.28 and 14.56 μM), in which there was more outstanding production of lipids in response to the stress caused by the metal, the intracellular levels of ROS dropped, suggesting that the increase in the total lipids content acted as a defense. The combination of the metals led to synergistic effects for the effective quantum yield and antagonistic for the total carbohydrates content of the alga, highlighting the importance of studies that consider metal interactions in ecotoxicological assessments. Mn and Cr led to different microalgae responses regarding the lipid class composition: Mn caused an increase in the levels of aliphatic hydrocarbons (HC), ketone (KET), free fatty acids (FFA), free sterol (ST), and acetone-mobile polar lipids (AMPL), while Cr induced a reduction in triglycerides (TAG), ST and AMPL. The data from this study contribute with information on the potential risks of Mn and Cr toxicity, isolated and combined, in freshwater ecosystems.